Strengthening the Preparedness of Elementary School Physical Education Teachers in Injury Prevention and Initial Emergency Response - Adi S; Cahyo Yuwono; Sugianto Parulian Simanjuntak; Dicky Budhi Setyawan; Jumanto; Ummi Nur Laila Sulistyani; Erika Afriana; Karina Permata Andhini (Universitas Negeri Semarang, 2026)
The limited preparedness of elementary school Physical Education (PE) teachers in managing injuries and emergency situations remains a significant challenge for ensuring student safety. This community service programme aimed to strengthen teachers’ competencies in injury prevention, emergency response, and school safety management through an integrated training and mentoring approach. The programme involved 33 PE teachers from the Physical Education Teachers’ Working Group (KKG PJOK) in Gunungpati Sub-district, Semarang, Indonesia. Activities included needs assessment, training on school safety management, injury prevention, first aid, Emergency Cardiac Care (ECC), cardiopulmonary resuscitation (CPR), simulation-based practice, the development of school safety Standard Operating Procedures (SOPs), and the implementation of SIGAPEdu as a digital injury reporting system. Programme effectiveness was evaluated using pre-test and post-test assessments, practical performance observations, and monitoring of programme outputs. The results demonstrated substantial improvements in teachers’ knowledge and practical competencies. The mean knowledge score increased from 58.24 ± 9.17 in the pre-test to 86.73 ± 6.84 in the post-test, representing an overall improvement of 48.9%. The proportion of teachers capable of performing basic CPR increased from 12.1% to 84.8%, exceeding the programme target of 80%. Furthermore, school-based safety SOPs were developed and implemented, three safety-oriented PE teaching materials were produced, and SIGAPEdu was adopted by 72.7% of participants, surpassing the predetermined target. These outcomes indicate that the programme successfully strengthened teachers’ emergency preparedness, promoted the integration of safety principles into PE learning, and supported the development of data-driven school safety practices. Continuous implementation of similar programmes is recommended to foster safer and higher-quality learning environments in schools.